Suspensão da exigibilidade do crédito tributário - Vargas, Luis Carlos A. Merçon de (2013)
This study aims to analyze the suspension of tax enforcement, discussed from a normative perspective. The method employed is the analytical-hermeneutics method, based on the premise that the law is constituted by language. For this reason, the work involves a syntactic, semantic and pragmatic analysis. The purpose is to comprehend the suspension of tax enforcement as a normative conditional proposition (i.e, as a formal structure). The antecedents of this proposition are the hypotheses listed in article 151, of the Brazilian Tax Code, and the consequent is the prohibition for the Tax Authority to collect tax credits. Furthermore, the paper also discusses the suspension norm s interactions among the other norms in the legal system, and how the sign-using agents of law deal with it. The work takes into consideration the complete formal structure of the legal norm (i.e., primary and secondary norms)